Saliva-derived components can enhance the performance of toluidine blue in photodynamic therapy - Macri, Nicolas; Dias, Luana Mendonça; Pavarina, Ana Claudia [UNESP]; Siqueira, Walter L.; Sperandio, Felipe Fornias (Frontiers, 2025)
Introduction: Oral Squamous Cell Carcinoma (OSCC) is the most common type of head and neck cancer worldwide. Currently, the most common treatment for OSCC includes a combination of surgery, radiation, and chemotherapy. However, despite the advances made in therapeutic strategies, the prognosis for patients diagnosed with OSCC remains poor, especially at later stages, which emphasizes the need for a novel treatment approach. Photodynamic therapy (PDT) has been employed as stand-alone or adjuvant therapy for OSCC. Methods: This study investigated the potential of using salivary proteins such as histatin-5 (Hst5) or derived peptides (RR14, DR9/RR14) to perform histatin-mediated PDT. The current literature has shown that histatins have the capacity to increase cellular membrane permeability, which indicates a potential synergistic effect when combined with a photosensitive agent. Toluidine Blue O (TBO) was used as the photosensitizer (PS) singularly combined with salivary peptides RR14, DR9/RR14, and Hst5 protein, and experiments were conducted to assess its biocompatibility and photodynamic effects on human gingival fibroblasts (FGH) and oral squamous cell carcinoma (SCC-25) cell lines. Results: The results showed that TBO concentrations below 4 μg/mL were non-cytotoxic to FGH cells, whereas concentrations up to 8 μg/mL were non-cytotoxic to SCC-25 cells. Also, the presence of histatins did not modify the absorption spectrum or photobleaching of TBO, enabling consistent production of reactive oxygen species (ROS) over time and rendering it as a stable and suitable PS for PDT. Further experiments also showed that when TBO was combined with Hst5, the ROS production increased by 186% compared to TBO alone. Conclusion: Results suggest that the use of histatin-enhanced PS offer a promising alternative to conventional PDT, potentially improving its outcomes.
Keywords: oral cancer (OC); oral pathology and oral medicine; photodynamic therapy; photosensitizer; saliva